A THINK-ALOUD PROTOCOLS AS A COGNITIVE STRATEGY TO INCREASE STUDENTS’ WRITING NARRATIVE SKILL AT EFL CLASSROOM - Purwo Trapsilo (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
The purpose of this study was twofold: its first aim was to know whether any differences of think-aloud potocols to develop writing narrative skill; second, to know whether which one is more effective to develop students’ writing narrative skill by using think-aloud protocols and traditional method.Students randomly assigned to an experimental and a control group. Treatment had three stages. In Stage 1, students were asked to write about a topic. InStage 2, students in the experimental group studied a model essay about that writing task and they hadthink-aloud protocol about those aspects of language that they noticed in the model essays. However inthe control group, students studied model essays for themselves and they did not have think-aloud part. InStage 3, students were asked to rewrite the writing task. The students in the experimental group showed that they got higher score in writing narrative by using think-aloud protocols than the control group. Furthermore, in the post test, experimental groupoutperformed the control group. The findings of the study suggest that thinking-aloud could be a goodstrategy for improving writing narrative performance.